Leveraging RISC-V to build an open-source (hardware) OS framework for reconfigurable IoT devices - Silva, Miguel Ângelo Fernandes (2021)
With the growing interest in RISC-V systems and the endless possi bilities of creating customized hardware architectures, we introduce the first proof of concept (PoC) implementation of ChamelIoT, the first open-source agnostic hardware operating system (OS) frame work for reconfigurable Internet of Things (IoT) low-end devices. At this stage, ChamelIoT, leveraging the Rocket Custom Co-Processor Interface (RoCC), provides hardware acceleration support for thread management and scheduling of three different OSes: RIOT, Zephyr, and FreeRTOS. This paper overviews the overall ChamelIoT archi tecture and describes the implementation details of the current PoC deployment. Our first experiments were carried out on a Xilinx Arty-35T FPGA Evaluation kit and the preliminary results are very promising, showing that the desired agnosticism and flexibility can be achieved with determinism and performance advantages at a reasonable cost of hardware resources.